A study on factor influencing customer purchasing decision through online shopping in Malaysia / Noor Amirah Sarimon and Syamimi Hamizah Shihaimi - Sarimon, Noor Amirah; Shihaimi, Syamimi Hamizah (Faculty of Business and Management, 2014)
The purpose of this study was to determine the factor influencing customer purchasing decision through online shopping in Malaysia. The variables consist of security, trust, usability and customer purchasing decision. The respondents were 100 employers and workers around Selangor and Malacca. The finding showed that security, trust, and usability have influence on the customer purchasing decision through online shopping in Malaysia. All variables show significance relationship towards the factor influencing customer purchasing decision through online shopping in Malaysia. This study refers to primary data and also secondary data for supporting the sampling technique. Meanwhile, the researcher use questionnaire as the method to collect all the data from sample respondents in accomplishing the research objectives. While the data for this study was analyzed using multiple statistical procedures: mean point value, standard deviation, and correlation analysis. The result of the study presented in this research agrees that security, trust, and usability can influence customer purchasing decision in online shopping. This study can be seen as a foreword to a more detailed study to be carrying by future research on the issue of the factor influencing customer purchasing decision through online shopping in Malaysia.